A rare cause of pneumothorax: Diesel aspiration pneumonitis - Ajay K Verma; Anubhuti Singh; Kislay Kishore; Surya Kant (Wolters Kluwer Medknow Publications, 2018)
Chemical pneumonitis refers to the aspiration of an inoculum that is inherently toxic to the lungs. Diesel aspiration is an uncommon cause of chemical pneumonitis, and aspiration leading to pneumothorax is an even rarer occurrence, not having been reported in adults so far. We are reporting a case of a young adult male who developed pneumothorax secondary to accidental diesel aspiration.